Non-volatile CBRAM/MIM switching technology for electronically reconfigurable passive microwave devices : theory and methods for application in rewritable chipless RFID /: theory and methods for application in rewritable chipless RFID. (2022) - Purushothama, Jayakrishnan Methapettyparambu; Perret, Etienne; Vena, Arnaud
No abstract available